Comparative study of the efficacy and safety of remimazolam and midazolam for general anesthesia in elderly patients: a randomized controlled trial - Yang Wan-jun; Geng Zhi-long; Gao Yuan-yuan; Cui Chao-yuan; Chen Zheng-ze; Tian Zi-wei; Guo Xi-lin; Zhang Ya-nan; Wang Lu; Huo Rui; Ma Chen-wei; Niu Jing (Perioperative Medicine)
Abstract Background Elderly patients are a vulnerable group with high perioperative risks. Thus, reducing the duration of anesthesia is important. Remimazolam is a benzodiazepine sedative commonly used for the induction and maintenance of general anesthesia given its rapid induction and rapid recovery. Most reports have focused on nonelderly patients. Aim To compare the time to loss of consciousness, length of PACU stay and incidence of adverse events in patients older than 65 years who received remimazolam for general anesthesia with those of patients who received midazolam. Methods This study was conducted at a university hospital between February 2022 and March 2023. We included 100 patients aged 65 years or older who were scheduled for surgery under general anesthesia. Patients were divided into 2 groups, namely, the midazolam group and the remimazolam group, with 50 patients in each group. The primary outcome was the time to loss of consciousness. The secondary outcomes included the time to extubation and length of PACU stay. We also recorded the percentage of flumazenil used and incidence of adverse events. Results Clinical data from 96 patients who were scheduled for surgery under general anesthesia were included in the final analysis, with 46 patients in the remimazolam group and 50 patients in the midazolam group. The time to loss of consciousness was 304 (222, 330) s in the remimazolam group and 95 (67, 25) s in the midazolam group, and the difference was significant (p = 0.000). The time to extubation was 24.93 ± 11.617 min in the remimazolam group and 34.88 ± 19.740 min in the midazolam group, revealing a significant difference (p = 0.003). The length of PACU stay was 55 (48, 64) min in the remimazolam group and 65 (55, 85) min in the midazolam group, and the difference was significant (p = 0.001). The percentage of flumazenil used was 6% in the remimazolam group and 20% in the midazolam group, and the difference was significant (p = 0.003). Conclusion General anesthesia with remimazolam has been shown to be effective and safe for surgery in elderly patients. The time to extubation was significantly shorter, length of PACU stay was shorter, and percentage of flumazenil used was lower in the remimazolam group than in the midazolam group.